Intensive Care Management of Preeclampsia: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Mentari Faisal Putri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The prevalence of preeclampsia is around 5% - 15% of all pregnant women. It can cause severe complications and even death in the mother and fetus if not adequately managed. Case presentation: A 36-year-old housewife was admitted to the emergency department with a chief complaint of shortness of breath before hospital arrival. The patient also complained of headaches. From the physical examination, consciousness was compos mentis, blood pressure 162/100 mmHg, HR 90 x/min, RR 24x/min, SpO 96%. From abdominal ultrasound gravid 36-37 weeks according to biometry, fetal alive, gemelli, intrauterine, transverse lie right head dorsoinferior- breech presentation, the Laboratory in emergency room result, haemoglobin: 10,4, leukocyte, 13.020, thrombocyte 359.000, hematocrit 31, ureum: 11, creatinin: 0.5, glucose: 72, protein urine: +2. Conclusion: In patients with preeclampsia, proper diagnosis and appropriate treatment in the intensive care unit and management by a multidisciplinary team can prevent preeclampsia complications and improve preeclamptic patients' outcomes.